Voting for Autocracy : Hegemonic Party Survival and its Demise in Mexico - Magaloni, Beatriz (Cambridge University Press, 2013)
In this book I provide a theory of how hegemonic-party autocracies sustain their rule and of the process by which those autocracies can undergo democratization, illustrating this theory with the case of Mexico